Синтез и биологические свойства 5,5-диметил-4-оксо-3,4,5,6-тетрагидробензо[h]хиназолин-2-ил) гидразонов дитерпеноида изостевиола - Маркосян, А. И.; Багдасарян, А. С.; Айвазян, А. С.; Габриелян, С. А.; Дангян, М. Ю.; Арсенян, Ф. Г.; Аракелян, А. Г. («Գիտություն» հրատ.)
Осуществлена конденсация 5,5-диметил-2-гидразинил-4-оксо-3,4,5,6-тетрагидробен-зо[h]хиназолинов с кетогруппами дитерпеноида изостевиола и его эфиров, синтезированы соответствующие гидразоны. Изучены противоопухолевые свойства в отношении саркома 180 и антибактериальные свойства синтезированных соединений в отношении грамположительных и грамотрицательных микроорганизмов. Առաջին անգամ իրականացվել է 5,5-դիմեթիլ-2-հիդրազինիլ-4-օքսո-3,4,5,6-տետրահիդրոբենզո[h]խինազոլինների կոնդենսումը դիտերպենոիդ իզոստևիոլի և նրա էսթերների կետոնային խմբերի հետ, և սինթեզվել են համապատասխան հիդրազոնները։ Ուսումնասիրվել են սինթեզված միացությունների հակաուռուցքային հատկությունները ուռուցքի սարկոմա 180 մոդելի վրա և հակաբակտերիալ հատկությունները գրամ-դրական և գրամ-բացասական միկրոօրգանիզմների նկատմամբ։ 2-Hydrazino-5,5-dimethyl-4-oxo-3,4,5,6-tetrahydrobenzo[h]quinazolines were condensed with (4R,6aR,9S,11bS)-4,9,11b-trimethyl-8-oxotetrahydro-6a,9-methanocyc-lohepta[a]naphthalene-4-carboxylic acid and its methyl, ethyl or benzyl esters. As a result of the reactions, (4R,6aR,9S,11bS)-8-(2-(5,5-dimethyl-4-oxo-3,4,5,6-tetrahyd-robenzo[h]quinazolin-2-yl)hydrazono)-4,9,11b-trimethyltetradecahydro-6a,9-metha-nocyclohepta[a]naphthalene-4-carboxylic acid or the corresponding esters. The antibacterial activity of the compounds was studied by the agar diffusion method using gram-positive strains of Staphylococcus aureus 209p, Bacillus subtilis ATCC 6633 and gram-negative bacilli Sh. Flexneri 6858, E. coli 0-55, with a bacterial load of 20 million microbial bodies per 1 ml of medium. The drug furazolidone was used as a positive control. In relation to gram-positive strains, 4 compounds showed a pronounced antibacterial effect (d=18-24 mm). In experiments with gram-negative strains, some compounds showed activity close to that of the control drug furazolidone. The antitumor properties of the compounds were studied in a mouse transplantable tumor model, sarcoma 180. The therapeutic effect was assessed by the percentage of tumor growth inhibition relative to the control. According to experimental data, the studied compounds in the doses used have weak antitumor activity and inhibit the growth of sarcoma 180 by 33-35%.
Keywords: Органическая и биоорганическая химия